1995
DOI: 10.1017/s095026880005843x
|View full text |Cite
|
Sign up to set email alerts
|

Priorities in global measles control: report of an outbreak in N'Djamena, Chad

Abstract: SUMMARYIn N'Djamena, capital of Chad, measles vaccination coverage of 12-23-monthold children fell from 61 % in 1990 to 15% in 1993. A community survey of measles after an outbreak in 1993 showed that among children < 5 years of age, the mean monthly attack rate was 37 per 1000 (95 % CI, 32-43) and the mean case fatality rate was 74%. Measles incidence was highest (77/1000/month) in children aged 9-11 months and fell among children > 3 years of age. Incidence rates were high (56/1000/month) among 6-8-month-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…The 2.8%–7.0% CFRs found in our study are as high as those reported in the early 1990s [3,16–20] from these same countries that were included in our surveys. Similar retrospective community studies conducted in Boukoki, Niamey, Niger after measles epidemics estimated an overall CFR of 6.6% in 1991 [16] and a CFR of 2.4% in children aged under 5 y in 1995 [17].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The 2.8%–7.0% CFRs found in our study are as high as those reported in the early 1990s [3,16–20] from these same countries that were included in our surveys. Similar retrospective community studies conducted in Boukoki, Niamey, Niger after measles epidemics estimated an overall CFR of 6.6% in 1991 [16] and a CFR of 2.4% in children aged under 5 y in 1995 [17].…”
Section: Discussionsupporting
confidence: 68%
“…A recent study in Mirriah district in Niger found a CFR of 9.7% [3]. In N'Djamena, a community survey after a measles epidemic in 1993 found a mean CFR of 7.4% in children aged under 5 y [20]. In an urban area of Nigeria in 1995, a CFR of 3.3% was found in the population [19].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] To our knowledge, no nationally representative study of measles CFRs has previously been conducted in a measles-endemic country.…”
Section: Introductionmentioning
confidence: 99%
“…Localized CFR estimates in south-east Asia 4,[9][10][11]13,15,16 and globally 3,[5][6][7][8]12,14,[18][19][20] have varied from less than 1% to 25%, but many studies were conducted before implementation of the Integrated Management of Childhood Illness strategy and recommendations to administer vitamin A to all measles cases. Therefore, many of these studies may not reflect the current situation.…”
Section: Introductionmentioning
confidence: 99%
“…Other than some rare isolates from Cameroon and Gabon from the early 1980s and The Gambia from the 1990s, no field isolates have been investigated in sub-Saharan West Africa [9][10][11]. Yet, children from this region may well experience some of the highest measles-related morbidity and mortality with case-fatality rates sometimes above 5% [12][13][14].…”
mentioning
confidence: 99%